Alcohol intake and incidence of coronary disease in Australian Aborigines - Burke, V.; Lee, Andy; Hunter, E.; Spargo, R.; Smith, R.; Beilin, L.; Puddey, I. (Oxford University Press, 2007)
Aims: To examine risk for coronary heart disease (CHD) and cardiovascular disease (CVD) in relation to alcohol in a cohort of Australian Aborigines. Methods: In 1988–1989, alcohol intake, drinking pattern, and beverage preference were elicited by interviewer-administered questionnaire in Western Australian Aborigines (258 men, 256 women) and cardiovascular outcomes ascertained through linkage to mortality and hospital admission records to 2002. Results: In proportional hazards models, risk for CHD, relative to lifetime abstainers, was significantly increased in ex-drinkers [Hazard ratio (HR) 2.29, 95% CL 1.23, 4.27], those drinking 41–60 g/day in men or 21–40 g/day in women (HR 2.80, 95% CL 1.04, 7.53), and those drinking >150 g/day for men or >100 g/day for women (HR 2.25, 95% CL 1.03, 4.90) with a J-shaped relationship. Low-to-moderate drinkers had lower waist girth, exercised more, and had a lower prevalence of overweight and smoking than at-risk drinkers. A preference for wine was associated with lower HR (0.28, 95% CL 0.10, 0.95). With CVD, only ex-drinkers showed significantly increased risk (HR 1.87, 95% CL 1.20, 2.91). Conclusions: More favourable health-related behaviours in low-to-moderate drinkers suggest that lower risk could be mediated by lifestyle, as proposed in other populations.